Transient analysis of bio-inspired vertical axis wind turbine - Ashwindran, Naidu Sandersagran (2020)
Energy harvesting signifies the development of industrial and power growth of economy and socio-economy in a region. The use of fossil fuels without proper regulation resulted in rise of greenhouse gases. Current wind turbine blades are designed to cater specific environment, geographical location and wind load. Hence, this resulted in poor and inadequate performance at inconsistent wind load regions such as Malaysia. Hence, design modification is being done on wind turbine blade morphology in order to adapt to various wind load environment. This aim of the present study is to investigate the performance of three proposed novel bioinspired wind turbine. Based upon the inconsistent wind speed in Malaysia due to the seasonal weather influence. Hence a novel blade design is being proposed to accommodate the wind speed potential of Malaysia. The proposed design is the product of design hybridization inspired by elements of nature. Thus, the theoretical computational fluid dynamic numerical investigation of the proposed turbines was conducted relative in 2D and based on theoretical assumption. Finite volume method approach was adapted to analyze the proposed turbines under non-conformal grid configuration. The proposed turbines are simulated under the similar computational configuration; numerical formulation; solver configuration. The transient numerical investigation is based on Unsteady Reynolds-averaged Naiver-Stokes equation and two equation turbulent transport numerical model. The turbines are analyzed in terms of power extraction coefficient (Cp), relative to Betz limit as benchmark. For simplicity the proposed turbines are labeled as Design 1; Design 2; Design 3. Design 1 is modelled in two scales which is large and microscale. Meanwhile Design 2 and Design 3 is modelled in microscale. The turbine is simulated under the influence of freestream velocity of 8 m/s as cut in speed for the turbines. Design 1 is simulated at five different low tip speed ratios. Results shows that the turbine responded well at λ = 0.2 and λ = 0.3 with positive power coefficient of Cp = 0.029 and Cp = 0.025 respectively which is relatively low in comparison to conventional drag driven turbines. Meanwhile, tip speed ratio, λ = 0.4, λ = 0.6 and λ = 0.9 indicated high instability in moment generation and high negative power extraction. Generated result indicates negative power coefficient which has impacted the performance of the turbine. The cavity vane experiences high adverse pressure due to its sharp cornered geometry in returning blade which consequently impacted the rotation of the advancing blade. Therefore, it is concluded that, design improvement needs to be done on the cavity vane geometry to ensure smooth transient in rotation without the blade affecting one another. As for Design 2 at λ = 1.3 the numerical oscillation stabilizes after 480° with an average stable peak value of Cm = 0.32. The average of total moment coefficient was Cm = 0.1886. Meanwhile, at λ = 1.7 the turbine generated an average moment coefficient value of Cm = 0.153991 and showed almost similar behaviour pattern as λ = 1.3 in wind energy extraction. The result showed that the proposed turbine with four blades composed of fixed AoA aerofoil NREL S819 performed well at λ = 1.3 and λ = 1.7 by generating a stable average power coefficient value of Cp = 0.245 and Cp = 0.262 respectively. Furthermore, the vorticity magnitude of each tip speed ratio was analyzed. It was observed that, wake effects induced by the trailing edge had affected the performance of the following blade. Meanwhile, Design 3 result shows that, design S-4 displayed numerical stability relative to the computational configuration and improved moment coefficient result compared to Savonius wind turbine. At λ = 0.59, the proposed wind turbine shows an improvement of 7.2% and reduces to 4% at λ = 0.94. Based on the computational fluid dynamic analysis of the proposed morphology indicates that design implementation via bioinspiration is liable but requires further analysis and experimental investigation for efficient and adaptive wind harvesting device.